Carbon-Supported Fe Catalysts for CO2 Electroreduction to High-Added Value Products: A DEMS Study: Effect of the Functionalization of the Support - S. Pérez-Rodríguez; G. García; L. Calvillo; V. Celorrio; E. Pastor; M. J. Lázaro (International Journal of Electrochemistry)
Vulcan XC-72R-supported Fe catalysts have been synthesised for the electroreduction of CO2 to high-added value products. Catalysts were obtained by the polyol method, using ethylene glycol as solvent and reducing agent. Prior to the metal deposition, Vulcan was subjected to different oxidation treatments in order to modify its surface chemistry and study its influence on the physicochemical and electrochemical properties of the catalysts, as well as on the product distribution. The oxidation treatments of the supports modify their textural properties, but do not affect significantly the physicochemical properties of catalysts. However, DEMS studies showed that the carbon support degradation, the distribution of products, and the catalytic activity toward the CO2 electroreduction reaction depend significantly on the surface chemistry of the carbon support.